¡Surge Peruano, Surge! Towards a cartography of independent fashion design in Peru. Issue 1 (1st October 2015) - Cuba, Lucia
This article explores notions of independent fashion design in Peru, addressing two actors within the local fashion design and textile systems that have played an important and relational role in its emergence: independent fashion designers and the Gamarra Commercial Emporium (or Gamarra) in Lima. Notions of independent fashion are explored in terms of their impact in contemporary fashion practices in Peru, aiming to go beyond a singular notion of independent fashion design. I will argue that a cartography of independent fashion design in Peru should account for the multiple voices and trajectories of the actors that shape it, considering independent fashion design as a movement of economic and affective dimensions. The article presents the story of Amapolay: Independent Manufacturers as a case study and one of many paths that shape the emerging fashion systems of independent design in Peru. It highlights the need to produce empirical research on emerging and independent design practices in the region, considering the experience of Peru as one of several national routes of independent design in Latin America that merit further study and theorization.